Fatigue performance of zirconia-reinforced Ti-6Al-4V nanocomposite processed by laser powder bed fusion: An improvement by hot isostatic pressing. (November 2022) - Guennec, Benjamin; Hattal, Amine; Hocini, Azziz; Mukhtarova, Kamilla; Kinoshita, Takahiro; Horikawa, Noriyo; Gubicza, Jenő; Djemaï, Madjid; Dirras, Guy
Graphical abstract: Highlights: Fatigue behavior of 1% nYSZ reinforced Ti-6Al-4V processed by L-PBF is studied. Stress relieved material exhibits modest fatigue strength due to fusion defects. HIP post-treatment almost doubles the fatigue endurance to reach σ max = 844 MPa. HIPed material shows plastic slip-induced fatigue crack nucleation without facets. Combined with high static strength, this mechanism should improve fatigue strength. Abstract: For the first time, four-point bending fatigue behavior of a Ti-6Al-4V alloy reinforced with 1 wt% nano-yttria-stabilized zirconia and processed by laser powder bed fusion was investigated. In a quest for clarification on the effect of the hot isostatic pressing (HIP) on the fatigue outcomes, both untreated and HIPed specimens were studied. The former material indicated relatively modest fatigue resistance mainly due to the presence of inherent processing defects, whereas the latter one revealed a promising fatigue strength in comparison with unreinforced Ti-6Al-4V and exhibited transgranular fatigue crack nucleation provoked by the crystallographic slip in long-length layers of α grain.